Temporal diversity of Taraxacum kok-saghyz plants reveals high rubber yield phenotypes - KATRINA CORNISH; STEVEN L. KOPICKY; SARAH K. MCNULTY; NIKITA AMSTUTZ; ANN M. CHANON; SONIA WALKER; MATTHEW D. KLEINHENZ; ALBERT R. MILLER; JOHN G. STREETER (Biodiversitas Journal of Biological Diversity, 2016)
Cornish K, Kopicky SL, McNulty SK, Amstutz N, Chanon AM, Walker S, Kleinhenz MD, Miller AR, Streeter JG. 2016. Temporal diversity of Taraxacum kok-saghyz plants reveals high rubber yield phenotypes. Biodiversitas 17: 847-856. Taraxacum koksaghyz is a diploid, out-crossing, rubber-producing species under development as an alternative natural rubber crop. About 17,650 seed were obtained from progeny of 20 wild collected plants. New populations of plants were developed in Ohio from a random subsample of these seed, which were then open pollinated. In November 2011, these seed were direct seeded in outdoor shallow raised beds and in high tunnel deep raised beds. Plants were harvested from the outdoor beds from July 2012 to July 2013 to provide temporal phenotypic data as plants developed and overwintered. The high tunnel beds were harvested July 2013, and provided data on 11 individual accessions, and their progeny, and on the effect of winter bed heating. Plants were highly variable. Rubber concentration in root tissue was not directly correlated with root, shoot or plant size. Across all growing conditions and developmental stage, the highest rubber yields per plant were found in plants with large roots combined with a large rosette, and an above average rubber concentration. These parameters appeared to segregate independently, and rubber concentration was heritable. Interbreeding plants selected for large root, large rosette and then high rubber concentration, should rapidly move Taraxacum kok-saghyz towards domestication and commercialization.